Trade Impacts of EU-ESA EPA Transitional Period On Malawi Sugar Exports - Nyirenda, Yalenga; Edriss, Abdi-Khalil; Phiri, Horace (European Scientific Journal, ESJ, 2017)
The renunciation of the Sugar Protocol between European Union (EU) and African, Caribbean and Pacific (ACP) countries in 2007 initiated a gradual reform process that will culminate into a reciprocal Duty Free Quota Free non-preferential access for all sugar producers in 2017. This paper analyzes how the reforms implemented this far have affected Malawi sugar exports. Since expansion of regional trade is seen as one of the adaptation measures for affected sugar industries. The study also analyzed the effect of regional integration areas. The results show that the EU sugar price reforms and elimination of country specific quotas had a positive influence of exports. Malawi being a low cost producer, it was not affected by falling prices and benefited to expanded access granted by a group safeguard. However, the production quotas for EU producers and high tariffs nonpreferred producers meant that Malawi was still shielded from competition that will prevail when the EU market is fully liberalized.